Character Building Based Islamic Education Through Zikr Era Society 5.0: Study of the Book of Fathul Arifin - Muhammad Fikri Rizqi Akbar; Kiki Ayu Hermawati; Nursiah; Sholahuddin Zuhri (al-Afkar, Journal For Islamic Studies, 2024)
This research describes character education through the implementation of remembrance in the Book of Fathul Arifin as an alternative to reducing the number of moral degradation in the era of the industrial revolution 4.0 towards society 5.0. The moral degradation is in the form of narcotics, theft, free sex, juvenile delinquency, and pornography. Harmonization of mind and heart education is a solution that can be used in this all-digital era. This research method uses a literature study with primary data from the Book of Fathul Arifin by Syekh Khatib as-Sambas, and secondary data in the form of journals and books. The results of this study describe that Society 5.0 is a complement to Revolution 4.0 by using Artificial Intelligence (AI) and making human life more practical. This progress has both positive and negative impacts. Dhikr education teaches humans to be balanced in their mindset, speech, and behavior. The remembrance education offered in the Book of Fathul Arifin is in the form of reading Al-Fatihah, Al-Ikhlas, Tahlil, Salawat, and Istighfar. The relevance of remembrance-based education to Society 5.0 is as a counterweight to humans in using technology wisely and not abusing it to view criminal or pornographic content.